The Legality of Earning Money from Online Games from an Islamic Perspective - Akbar, Taufik (MOVE: Journal of Community Service and Engagement, 2024)
Online gaming has become increasingly popular in Indonesia, especially among young people, with 63.9 million users. While online gaming can be a source of income, there are concerns about its permissibility in Islam. Islamic scholars state that earning money from online games is permissible as long as it is done ethically and the games do not involve prohibited elements such as gambling, violence, or pornography. To address this topic, a discussion was held at SMK Al Ihsan in West Jakarta. The results of the workshop indicate that online gaming can be a positive and permissible activity if it adheres to Islamic principles.